Radioiodine Dosimetry for Benign and Malignant Thyroid Disease - Al Jabri, Amna Juma (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
Thyroid diseases are a common clinical disorder with 5-10% diagnosed as thyroid cancer. The published guidelines that provide clinical guidance for the diagnosis, treatment and management of thyroid diseases, based on a range of clinical studies, contain some inconsistent recommendations with considerable uncertainties evident across literature. This thesis investigated some novel approaches to, and analysis of, personalised benign and cancer treatments of thyroid disorders at St James's Hospital patients, Ireland, using radioactive iodine, I-131. I-131 activities can be administered either using a fixed activity approach or by personalised activity approach. For benign thyroid disease, the successful outcome of I-131 treatment is reached by restoring normal thyroid function or achieving a hypothyroid state that requires lifelong medication. Recent studies have shown that personalised I-131 treatment reduces the risk of hypothyroidism. The European Association of Nuclear Medicine (EANM) dosimetry protocol for benign thyroid disease treatment recommends that an I-131 tracer capsule is administered followed by a subsequent thyroid percentage uptake measurements. This thesis investigated the possibility of measuring thyroid percentage uptake using Technetium-99m (Tc-9mm), through a retrospective study of 143 patients diagnosed with hyperthyroidism. The study concluded that a significant correlation existed between thyroid uptakes measured using I-131 and Tc-99m, however, there was a significant difference between the genders. In addition, in this thesis, the available factors affecting the outcome of I-131 benign thyroid disease therapy were evaluated in a retrospective study of 92 patients. The analysis failed to demonstrate a difference between the fixed activity versus the personalised dosimetry administration approaches for the investigated outcomes. Several clinical parameters were identified as significantly increasing the probability of restoring a euthyroid state, including patient age, gender, TSH level and thyroid uptake at 24 hours. Further in this work, an adapted version of the EANM blood and bone marrow dosimetry protocol for remnant ablation of thyroid cancer was implemented for 13 patients, prepared with Thyrogen administration. The study showed strong predictability of therapeutic absorbed doses using a pre-therapeutic absorbed dose evaluation using I-131, thus indicating the methods potential for personalised therapy. A further investigation in this thesis examined whether blood micro-sampling for I-131 therapy dosimetry evaluation could replace the standard blood sampling approach. The study, using 34 blood samples post administering diagnostic or therapeutic activity of I-131, validated the use of the finger-prick method as an alternative blood-collection approach. Finally, the radiation dose rates to staff members, while in close proximity to the patients for blood sampling post I-131 therapeutic administration, were investigated using Monte Carlo simulations which showed the approach as an accurate method of dose rate estimation, providing a reliable risk assessment for new practices or retrospective dose estimation. The estimated dose rates for different patient circumstances may also offer data for determining patient suitability for dosimetry at high activities of I-131.
APPROVED
Keywords: Thyroid; Hyperthyroidism; Thyrotoxicosis; I-131; Radioiodine; EANM; Dosimetry